1990
DOI: 10.1002/dev.420230806
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postnatal maternal stress on blood pressure and heart rate of juvenile and adult rat offspring

Abstract: Post--not prenatal maternal stress disrupts BP and HR control in rat offspring; disruption is greater after restraint than injection. There is sympathetic hyperactivity in preweanlings and hypoactivity in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To our knowledge, one study conducted by Mills, Bruckert, and Smith (1990) reported that postnatal maternal restraint increased sympathetic activity in preweaning rats and induced a locomotor hypoactivity in adult animals. Moreover, maternal nutritional stress during the perinatal and lactational periods was reported to change the endocrine profile of the offspring (Leonhardt et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…To our knowledge, one study conducted by Mills, Bruckert, and Smith (1990) reported that postnatal maternal restraint increased sympathetic activity in preweaning rats and induced a locomotor hypoactivity in adult animals. Moreover, maternal nutritional stress during the perinatal and lactational periods was reported to change the endocrine profile of the offspring (Leonhardt et al, 2002).…”
Section: Introductionmentioning
confidence: 95%